Educational Software for Creative Learning in the Comparative Embryology Course - Dedsy Francisca Villegas-García (Universidad Nacional, Costa Rica, 2011)
This study aimed to diagnose the necessity of educational software on the segmentation process in animals, to stimulate students' creative learning in the Comparative Embryology course, at University of Experimental Pedagogy, campus Barquisimeto (UPEL-IPB) Lara State, Venezuela. This is a field descriptive research, whose study subjects were 32 students taking the Comparative Embryology course during the I-2009 term. A Likert-type questionnaire was designed and applied. Experts in the area confirmed its validity, and its reliability was determined through the Cronbach's Alpha coefficient. The data was treated through descriptive statistics (collection, analysis and interpretation), obtaining frequency charts and percentages for presentation. The outcomes demonstrated a high necessity of Comparative Embryology students to have educational software for creative learning, an electronic resource adapted to new communication and information technologies.